Особливості формування системи інформаційної безпеки українських підприємств за високо динамічних умов цифровізації - Озарко, К.С.; Копитко, С.Б. (Економічний вісник Донбасу, 2023)
В роботі визначено актуальність досліджуваної проблеми стосовно розвитку систем інформаційної безпеки українських підприємств за високо динамічних умов цифровізації. Адже за умов стрімкого розвитку цифрової економіки (її цифровізування) економічний розвиток підприємств все більше залежатиме не від матеріальних, а від інформаційних ресурсів. Цілі дослідження полягали у дослідженні проблематики інформаційної безпеки українських підприємств в умовах цифровізації, розробленні рекомендацій і пропозицій щодо вирішення існуючих проблем. В праці запропоновано комплексну систему цифрової безпеки вітчизняних підприємств за високо динамічних умов господарювання. Рівень ефективності функціонування системи забезпечення інформаційної безпеки підприємства визначає ступінь досягнення цілей цифрового трансформування. Активізування ж процесів цифрового трансформування викликає необхідність для формування, застосування, удосконалення підприємствами засобів забезпечення інформаційної безпеки. The paper determines the relevance of the problem under study with regard to the development of information security systems of Ukrainian enterprises under highly dynamic conditions of digitalization. After all, in the context of the rapid development of the digital economy (its digitalization), the economic development of enterprises will increasingly depend not on material but on information resources. The aims of the study were to investigate the issues of information security of Ukrainian enterprises in the context of digitalization, to develop recommendations and proposals for solving existing problems. Issues related to ensuring the necessary (sufficient) level of economic security of enterprises and organizations are becoming increasingly relevant, as the information environment is characterized by an increasingly high level of dynamism. In the face of rapid changes due to the digitalization of the economy, domestic businesses need to timely develop systems to identify, assess, avoid or minimize potential risks and threats. The authors uses the following research methods: comparison, observation, analysis and synthesis.
It is critical to form and use a digital security system by domestic enterprises in a highly dynamic economic environment. That is why the paper proposes a comprehensive system of digital security of domestic enterprises in highly dynamic economic conditions. The level of efficiency of the enterprise information security system determines the degree of achievement of the goals of digital transformation. The intensification of digital transformation processes necessitates the formation, application, and improvement of information security tools by enterprises. The practical significance of the recommendations is that the economic security of an enterprise depends on the level of information security of digital transformation. To ensure the necessary (permissible) degree of information security of digital transformation, enterprises need to take actions of the management system aimed at optimizing the management system, functions, methods of activity, management decisions, etc. through the use of information (digital) technologies.